1981
DOI: 10.1017/s0022172400069552
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasmosis and the wild rabbit Oryctolagus cuniculus in Victoria, Australia with suggested mechanisms for dissemination of oocysts

Abstract: SummarySera or serum eluates from 1697 wild rabbits [Oryctolagus cuniculus (L)], collected over the past 10 years from 24 sites in 5 geographic regions of Victoria, were examined for antibodies to Toxoplasma gondii. Sera generally were classified into three broad groups, negative (titre < 10), weakly reactive (titre 10 to 100) and strongly positive (titre > 1000). Strongly positive sera came from rabbits collected in a small number of localized areas, most significantly the Melbourne and Metropolitan Boa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…35,36 Contaminated soil is an important source of infection for humans, herbivores, rodents, and birds. [37][38][39][40] Although conclusive evidence about survival of T gondii oocysts after sewage treatment is not yet available, results of 2 studies 41,42 suggest that exposure to sewage effluent or waste is associated with increased risk for T gondii infection in humans or other animals. Until more definitive information is available, cat feces should not be flushed down the toilet, even if the litter is flushable.…”
Section: Small Animalsmentioning
confidence: 99%
“…35,36 Contaminated soil is an important source of infection for humans, herbivores, rodents, and birds. [37][38][39][40] Although conclusive evidence about survival of T gondii oocysts after sewage treatment is not yet available, results of 2 studies 41,42 suggest that exposure to sewage effluent or waste is associated with increased risk for T gondii infection in humans or other animals. Until more definitive information is available, cat feces should not be flushed down the toilet, even if the litter is flushable.…”
Section: Small Animalsmentioning
confidence: 99%
“…The T. gondii seroprevalence in rabbits at Pitroddie is the lowest yet reported in wild rabbits. Previous authors found seroprevalences of 5% in the Czech Republic (Hejlícek et al 1997), 11·9 and 14·2% in Spain (Almería et al 2004; García-Bocanegra et al 2010 a , b ), 17·4% in Australia (Cox et al 1981), 21% in Norway and Sweden (Kapperud, 1978), 50% in Wales (Beverley et al 1954), and a PCR prevalence of 68·4% in England (Hughes et al 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Very low seroprevalence at Pitroddie may be due to few feral cats being present. Previously, T. gondii oocysts or infections have been reported where cats were present (Sroka et al 2006) and where traces of their feces could have been carried on straw (Faull et al 1986) or in water (Cox et al 1981; Aramini et al 1999; Conrad et al 2005), but rarely where cats were absent (Dubey et al 1997). Straw is not routinely imported to Pitroddie and waterborne T. gondii has not been reported there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Asymptomatic T. gondii infections are widely prevalent in many small mammals including rats (Dubey and Frenkel, 1998); various species of mice (Dubey and Beattie, 1988;Brillhart et al, 1994, Smith andFrenkel, 1995), and rabbits (Cox et al, 1981;Dubey and Beattie, 1988;Dubey et al, 1992a) but clinical toxoplasmosis is relatively rare. We are not aware of any reports of clinical toxoplasmosis in naturally infected rats and mice.…”
Section: Toxoplasmosis In Small Mammalsmentioning
confidence: 99%